Do clinical guidelines for whole body computerised tomography in trauma improve diagnostic accuracy and reduce unnecessary investigations? A systematic review and narrative synthesis. (July 2017) - Hare, Nicholas P; Macdonald, Alistair W; Mellor, James P; Younus, Maaz; Chatha, Hridesh; Sammy, Ian
Introduction: Whole body computerised tomography has become a standard of care for the investigation of major trauma patients. However, its use varies widely, and current clinical guidelines are not universally accepted. We undertook a systematic review of the literature to determine whether clinical guidelines for whole body computerised tomography in trauma increase its diagnostic accuracy. Materials and methods: A systematic review of Medline, Cinhal and the Cochrane database, supplemented by a manual search of relevant papers was undertaken, with narrative synthesis. Studies comparing clinical guidelines to physician gestalt for the use of whole body computerised tomography in adult trauma were included. Results: A total of 887 papers were identified from the electronic databases, and 1 from manual searches. Of these, seven papers fulfilled the inclusion criteria. Two papers compared clinical guidelines with routine practice: one found increased diagnostic accuracy while the other did not. Two papers investigated the performance of established clinical guidelines and demonstrated moderate sensitivity and low specificity. Two papers compared different components of established triage tools in trauma. One paper devised a de novo clinical decision rule, and demonstrated good diagnostic accuracy with the tool. The outcome criteria used to define a 'positive' scan varied widely, making direct comparisons between studies impossible. Conclusions: Current clinical guidelines for whole body computerised tomography in trauma may increase the sensitivity of the investigation, but the evidence to support this is limited. There is a need to standardise the definition of a 'clinically significant' finding on CT to allow better comparison of diagnostic studies.